Precisiones sobre la fundación del colegio de la Compañía de Jesús en Villafranca del Bierzo - Campos Sánchez-Bordona, María Dolores (Estudios humanísticos. Geografía, historia y arte, 1998)
This project shows the 1st fundantion of the college of the Jesuits in Villafranca del Bierzo ( Léon) in the XVI century. Sir Pedro Alvarez de Toledo, Marqués de Villafranca, master person who brought the Jesuits to this town, and who gave economic resources for the construccion of the college. This foundation went on 1614 being in this case Gabriel de Robles who gave the economic resource.